Ethical consumerism and comparative studies across different cultures emerging research and opportunities - Al-A'Ali, Ebtihaj Ahmad, 1957-; Masmoudi, Meryem, 1979- (Advances in business strategy and competitive advantage., 2020)
"This book examines ethical consumerism in business"--